RENAL DISEASES: CAREGIVERS' KNOWLEDGE, ATTITUDE AND PRACTICE IN NORTH EASTERN NIGERIA - Yauba MS; Akuhwa RT; Farouk AG; Mustapha MG; Ummate I; Ibrahim BA; Machoko Y; Bello M (Ntec Specialist, 2017)
Lack of awareness of renal diseases among the parents/care givers of children can contribute to the development of childhood chronic kidney disease (CKD). Awareness of kidney disease by the care givers of children can improve their health seeking behaviour and reduce the significant economic and public health burden. We conducted a cross-sectional descriptive study to assess the knowledge, attitude and practice of renal diseases among the care givers of children attending University of Maiduguri Teaching Hospital. Management of CKD is very expensive especially in the third world where most care givers are poor and cannot afford the cost of renal replacement therapy like dialysis and renal transplant. This underscores the determination of knowledge, attitude and practice of parents/care givers on childhood renal diseases. Objective: To assess the knowledge, attitude and practices on renal diseases among the care givers of children attending a tertiary hospital in north eastern Nigeria. Method: This cross-sectional study was conducted among mothers or caregivers of children receiving care in the Department of Paediatrics of a Teaching Hospital, Borno state. Mothers/caregivers were consecutively selected as they come to the hospital and 420 subjects were interviewed through a self-administered questionnaire. Each subject was interviewed on his or her knowledge, attitude and practice of childhood renal diseases and data was entered appropriately into the different sections of the study questionnaires. Data was analysed using Epi-info statistical software (version 7.0). Informed consent was obtained from the parents and confidentiality to any information disclosed by the mother was ensured. Results: The ages of the respondents ranged from 18 - 67 years with a mean age of 37.2 (SD±13.6) years. Majority 140 (33.3%) of the respondents were aged 31 - 50 years; p less than 0.05. Among the respondents, were 255 (60.7%) females and 165 (39.3%) males with male to female ratio of 1: 1.5. The ages of the children ranged from 1 month to 15 years with 239 (56.9%) males and 181 (43.1%) females and male to female ratio of 1.3: 1. There were 267 (63.6%) Muslims and 153 (36.4%) Christians. There were 98 (23.3%) care givers from the upper social class, 120 (28.6%) from the middle social class and 202 (48.1%) from the lower social class. Most mothers (89.2%) had no factor preventing them from seeking medical care. Many (70.7%) of the caregivers took their children to health facilities once sick or developed any symptom of severe childhood disease. Conclusion: Although most of the care givers that participated in this study had knowledge of one form of kidney disease or the other, most had no knowledge of any treatment modality of these kidney diseases